Individual patterns of response to traditional and modified sprint interval training - Schulhauser, K. T.; Bonafiglia, J. T.; McKie, G. L.; McCarthy, S. F.; Islam, H.; Townsend, L. K.; Grisebach, D.; Todd, C.; Gurd, B. J.; Hazell, T. (Journal of Sports Sciences, 2021)
We compared the incidence of response between a traditional sprint interval training (SIT) protocol (30:240: 4-6 x 30-s, 240-s recovery) and 2 modified SIT protocols (15:120: 8-12 x 15-s, 120-s recovery; 5:40: 24-36 x 5-s, 40-s recovery) over 4 weeks of training in 84 recreationally active individuals (n = 23 per SIT group/15 control participants). Pre- and post-testing measures included VO2max, 5-km time trial, and anaerobic capacity. Responders were classified using 2x typical error and seven other approaches to explore the impact of classification method on response rates. There was no difference in the proportion (2x typical error) of VO2max responders across groups (30:240: 64%; 15:120: 39%; 5:40: 41%; CTRL: 33%; P= 0.190). The 30:240 group had more responders (P< 0.05) for time trial performance (70%) and peak speed during the 30 s running test (48%) compared to CTRL (21% and 0%, respectively). There were no other between-group differences (P> 0.112). Approaches with the largest response thresholds resulted in the fewest responders highlighting response rates are influenced by the method used. Additionally, we observed intra-individual differences in responsiveness across outcomes. This is the first study to empirically test the difference in the incidence of response and demonstrate individual patterns of response across different SIT protocols.